Strengthening Startup Regulation to Advance Sustainable Economic Development in Uzbekistan - Akbar Zafar Ogli Tojiboev; Kambariddin Miradxamovich Mekhmonov; Sokhiba Fazilovna Inoyatova; Dilorom Khaitbayevna Rakhimova; Farrukha Fakhriddinovna Mukhitdinova (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
The development of the digital economy has generated new forms of entrepreneurship, innovative business models, and investment mechanisms closely associated with startup activities. Despite the growing importance of startups in driving innovation and economic growth, their development in Uzbekistan has not been supported by an adequate regulatory framework capable of ensuring legal certainty and fostering a sustainable startup ecosystem. Therefore, research on startup regulatory reform is necessary to support sustainable economic development. This study aims to, first, identify the legal issues and regulatory challenges affecting startups in Uzbekistan; second, analyze the ideal startup regulatory model in the United States as a comparative reference; and third, formulate startup regulatory reforms to promote sustainable economic development. This research uses a normative legal research method using statutory, comparative, and conceptual approaches. The findings reveal that first, the principal challenge facing startup development in Uzbekistan is the lack of a comprehensive and integrated legal framework specifically governing startups, resulting in legal uncertainty and limiting ecosystem growth. Second, the experience of the United States demonstrates that a successful startup ecosystem depends on adaptive and innovation-oriented regulations that facilitate access to funding, provide effective legal protection, and encourage digital economic activities. Third, startup regulatory reform in Uzbekistan should be pursued through the enactment of a Startup Act, harmonization of startup-related regulations within the national legal system, simplification of bureaucratic procedures, and strengthening institutional support through startup incubators involving legal and financial experts. These measures are expected to enhance legal certainty, attract investment, stimulate innovation, and promote sustainable digital economic development in Uzbekistan.